EVALUASI KEGIATAN PENANAMAN TANAMAN KARET DI KPHP MODEL DOLAGO TANGGUNUNG DESA OLO BARU KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Pidu, Mohamad Zulhi Apriyanto; Hamzari, Hamzari (Jurnal Warta Rimba, 2020)
Forest areas in the Model Dolago Tanggunung KPHP area, Olo Baru Village, South Parigi Regency, Parigi Moutong Regency are now indicated to have been damaged due to activities carried out by communities in and around the forest area. Therefore, Dolago Tanggunung KPHP established Olo Baru Village as an effort to rehabilitate forests and land, an effort that must be made, namely the rubber tree planting program and the land used for rubber tree planting. The purpose of this study was to evaluate rubber planting activities in the area of the KPHP Model Dolago Tanggunung, Olo Baru Village, South Parigi District, Parigi Moutong District. This research was conducted for three months, from January to March 2019. The research location was located in Olo Baru Village, South Parigi Regency, Parigi Moutong Regency. In this study the data collection techniques used were observation and interviews (questionnaire) data collection using questionnaires and interview guidelines, respondents selected deliberately (purposive) consisting of: rubber farmer groups (20 people). The study uses descriptive qualitative and quantitative methods. Based on the results of the study it can be concluded as follows: Development of rubber plants in the KPHP Model Dolago Tanggunung Olo Baru, South Parigi Village, Parigi Regency, Moutong Regency has gone according to plan in nursery activities (100%), planting (100%)), maintenance (100%), protection and protection (100%), seed requirements and alternative seed procurement (100%), group institutions (85%), technical guidance (90%), There is one activity that has not been maximally realized, namely counseling and mentoring (25%) .Kata Kunci : KPHP Area Of The Dolago Tanggunung Model